Biological and transcriptional studies reveal VmeL is involved in motility, biofilm formation and virulence in Vibrio parahaemolyticus - Liu, Peng-xuan; Zhang, Xiao-yun; Wang, Quan; Li, Yang-yang; Sun, Wei-dong; Qi, Yu; Zhou, Kai; Han, Xian-gan; Chen, Zhao-guo; Fang, Wei-huan; Jiang, Wei (Frontiers in Microbiology, 2022)
Vibrio parahaemolyticus is a marine pathogen thought to be the leading cause of seafood-borne gastroenteritis globally, urgently requiring efficient management methods. V. parahaemolyticus encodes 12 resistance/nodulation/division (RND) efflux systems. However, research on these systems is still in its infancy. In this study, we discovered that the inactivation of VmeL, a membrane fusion protein within the RND efflux systems, led to reduction of the ability of biofilm formation. Further results displayed that the decreased capacity of Congo red binding and the colony of ΔvmeL is more translucent compared with wild type strains, suggested reduced biofilm formation due to decreased production of biofilm exopolysaccharide upon vmeL deletion. In addition, the deletion of vmeL abolished surface swarming and swimming motility of V. parahaemolyticus. Additionally, deletion of vmeL weakened the cytotoxicity of V. parahaemolyticus towards HeLa cells, and impaired its virulence in a murine intraperitoneal infection assay. Finally, through RNA-sequencing, we ascertained that there were 716 upregulated genes and 247 downregulated genes in ΔvmeL strain. KEGG enrichment analysis revealed that quorum sensing, bacterial secretion systems, ATP-binding cassette transporters, and various amino acid metabolism pathways were altered due to the inactivation of vmeL. qRT-PCR further confirmed that genes accountable to the type Ⅲ secretion system (T3SS1) and lateral flagella were negatively affected by vmeL deletion. Taken together, our results suggest that VmeL plays an important role in pathogenicity, making it a good target for managing infection with V. parahaemolyticus.